2013
DOI: 10.1038/modpathol.2012.151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic values between combined immunohistochemical score of estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, Ki-67 and the corresponding gene expression score in breast cancer

Abstract: In the clinical diagnosis of breast cancer, immunohistochemistry panels with estrogen receptor (ER), progesterone receptor (PgR), human epidermal growth factor receptor 2 (HER2) and Ki-67 are routinely used, and they have been proposed for the classification of breast tumors into distinct subtypes. Gene expression analysis with formalin-fixed paraffin-embedded material have also become widely available recently, but the prognostic values of corresponding gene panels compared with these four immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…ER, PR and HER2/neu expression was negative in majority of cases which correlated with other Indian studies by Kuraparthy et al, [16] and Verma et al, [10]. International studies were showing hormone receptor positivity and HER2/neu negativity [11][12][13]. Immunohistochemical expression of lymph node metastasis from IDC cases were mainly ER, PR and HER2/neu negative.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…ER, PR and HER2/neu expression was negative in majority of cases which correlated with other Indian studies by Kuraparthy et al, [16] and Verma et al, [10]. International studies were showing hormone receptor positivity and HER2/neu negativity [11][12][13]. Immunohistochemical expression of lymph node metastasis from IDC cases were mainly ER, PR and HER2/neu negative.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, out of 185 mastectomy specimen, 41.67% cases were associated with axillary lymph node metastasis. This correlated with other Indian and international studies [10][11][12][13][14][15]. In view of rising incidence of breast cancer in India, a thorough assessment of mastectomy and axillary lymph node biopsies is essential.…”
Section: Discussionmentioning
confidence: 89%
“…One study suggests that the amount of prognostic information contained in four widely performed immunohistochemical (IHC) assays is similar to that in a multi-gene test [35]. Moreover a study comparing several multi-gene tests to IHC4 (using semiquantitative assessment) showed that the IHC4 score provides better prognostic information than the corresponding quantitative RNA measurements [36]. Thus the combination of quality controlled conventional IHC tests and multigene signatures may provide more information for some patients at intermediate risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Normal mouse immunoglobulin (DAKO, Glostrup, Denmark) was used as a negative control and no signal was observed in those control sections. Data regarding the Ki-67 labeling index, as well as the statuses of ER, PgR, and Her2, were previously evaluated by our research group [19, 20]. CD68-, CD169-, and CD8-positive staining was counted in four randomly selected fields-of-view by two pathologists (TS and YM) who were blind to patient information.…”
Section: Methodsmentioning
confidence: 99%